The protection of animals in the Italian Constitution (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The essay explores the innovative scope of the constitutional reform that inserted the principle of animal protection into the Constitution. The provision of a principle of direct protection implies the recognition of animals as “sentient beings” and accepts the perspective of the principle of responsibility. The inclusion among the Fundamental Principles of the Constitution stabilizes the most advanced points of the regulatory-jurisprudential evolution and shifts the axis of the balance between human and animal interests, imposing a more rigorous use of the criteria of proportionality and justifiability of the fields and methods of use of animals. The provision of a state law reserve clarifies that the “protection of animals” is a matter in its own right, which is characterized by a physiological state exclusivity and a natural transversality (destined to intersect matters of regional competence).
Keywords: Constitution; animals; protection; responsibility; competence